ANALISIS TINGKAT LITERASI MEDIA EFEKTIFITAS MEDIA PENYULUHAN TERHADAP PETANI KELAPA SAWIT DI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Hygeni Sianturi; Roza Yulida; Yulia Andriani (Fakultas Pertanian, Universitas Riau, 2020)
This research aims to 1) identify the characteristics of farmers and extension of oil palm in Langgam district, 2) identify palm oil extension media in Langgam district; 3) analyze the level of literacy ability of farmers and palm oil extension in Langgam district; 4) analyze effectiveness level media extension on oil palm farmers in Langgam district. The researchwas conducted in Langgam district of Pelalawan Regency, 75 samples were taken to answer the first objective using Likerts Summated Rating Scale (LSRS) scale, the second objective was to look at oil palm extension media using descriptive analysis, the third objective is to see literacy ability of farmers and extension using Likerts Summated Rating Scale (LSRS) scale, the fourth objective is to see the extent of effectiveness of the extension media measurable by using the EPIC model with the Likerts Summated Rating Scale (LSRS) scale. Internal characteristics of oil palm farmers in Langgam district Pelalawan regency in terms of age is a productive workforce. Education level of farmers of junior high and elementary school. The average number of dependents of farm households is in small family groups. The percentage of farming experience included in the category is quite experience. The land area of farmers is located on medium land, cosmopolity included in the high category. The external characteristics of oil palm farmers in Langgam district Pelalawan regency are categorized as high. The level of literacy ability of the media of farmers is at the basic level and the level of literacy ability is at the advanced level. Media extension is the media in the form of printed media and audio visual media.